Animation Design for Garbage Recycling in Yogyakarta - Mr. Riswanto S1 (Saraswati)
Definision of Animation in a guidebook “Animation Workshop Guide,written by Robi Angler, word Animation is taken from Latin language“anima”, itmeans a soul or vital breath. Animation often to be defined as an activity toenlive from static object then can make some movements or only make animpression to describe that the object moves as if it is doing by itself. Mostly,animation talks about form of an object that can change to create movement andlife. So, this definitinion explains that animation can create something to becomelife or move. In English-Indonesian Dictionary by John M. Echols and HasanSadily, Animate is something life, soul: (1) to enlive, to be soul, to flush, tosplendor, Animated: (1) exciting, (2) life, Animation, (noun). Spirit, splendor,happiness.This final assignment design is tittled “Educational Animation Design forGarbage Recycling in Yogyakarta”. This is a presentation design to convey aboutgarbage problems generally, garbage problem in Yogyakarta city, causalities andsolutions that can be done to this garbage problem. Presentated by animation,there is no main character or human characterization inside, all animated objectsare iconic or symbolic form as illustration to describe messages that want to beconveyed. This Presentasion uses compound animation techniques betweenmotion graphic animation and 3D animation.This animation presentation design is made in a cooperation with BLH ofYogyakarta city as data source and finally this design artwork will be used byBLH as the media for education and counseling or can be used for other needs tosupport garbage recycling programs independently in Yogyakarta city.Keywords: Garbage, Education, Yogyakarta.